2014
DOI: 10.17221/77/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Forest management and snag characteristics in Northern Iran lowland forests

Abstract: Some snag characteristics were studied in three different Hyrcanian lowland forests. The highest snag density (38.4 stem·ha -1 ) was found in fully protected forests, and it was significantly higher than in selectively logged (23.7 stem·ha -1 ) and open access forests (8.8 stem·ha -1 ). The snag volume, diameter and height were also significantly higher in the fully protected forests. The number of snag species was recorded in fully protected (9), selectively logged (5) and open access forests (4). The snags w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 73 publications
(77 reference statements)
2
13
0
Order By: Relevance
“…These findings are in accordance with those reported by Tavankar et al (2014) in an unmanaged compartment of the Caspian Forest, but in contrast with those by Behjou et al (2014) who found differences due to forest management in the Guilan province forests.…”
Section: Single-tree Selection Cutting Effect On Cwd In Mixed Standssupporting
confidence: 93%
“…These findings are in accordance with those reported by Tavankar et al (2014) in an unmanaged compartment of the Caspian Forest, but in contrast with those by Behjou et al (2014) who found differences due to forest management in the Guilan province forests.…”
Section: Single-tree Selection Cutting Effect On Cwd In Mixed Standssupporting
confidence: 93%
“…This species, in terms of volume, mostly contributed to the CWD in the three accessibility classes. In general observations, CWD mirrored the species composition of the area, as also observed in lowland forests in Iran [20]. The results revealed that the volume of different botanical species of CWD is proportional to the different species of the standing trees.…”
Section: Species Of Cwdsupporting
confidence: 71%
“…In the lowland forest in Iran, similar results were found. Tavankar et al [20] observed that in open access forest, the snag number and volume were lower than in selectively-logged and in fully protected forest.…”
Section: Components Of Cwdmentioning
confidence: 99%
“…To account for edges and to minimize the bias in the calculation of the species mingling index (as in [34]), all trees within a certain distance of the edge of the plot may not be included in the computation of MDn; therefore, the species mingling index may be based on the following: (10) where Te = the set of trees in a stand that are inside the assumed edge buffer.…”
Section: Discussionmentioning
confidence: 99%
“…Natural development of some forests in the absence of major disturbances can lead to increases in the species mingling index, and thus, the structural development of unmanaged forests might be used as a reference for planning [4]. While generally applied to live trees, the mingling concept has also been applied to the presence of snags (dead trees) in an assessment of the natural condition of forests [9] and would seem to complement other resource measurements regarding the ecological characteristics of forests [10] and to help assess forest biodiversity [11].…”
Section: Introductionmentioning
confidence: 99%